The Open Data Movement: Young Activists between Data Disclosure and Digital Reputation - Arcidiacono, Davide; Reale, Giuseppe (PARTECIPAZIONE E CONFLITTO, 2017)
Young citizens show an increasing interest for direct democracy tools and for the building of a new relationship with public administration through the use of digital platforms. The Open Data issue is part of this transformation. The paper analyzes the Open Data issue from the perspective of a spontaneous and informal group of digital activists with the aim of promoting data disclosure. The study is focused mainly on the case of a specific local movement, named Open Data Sicilia (ODS), combining traditional ethnographic observation with an ethnographic approach. The aim of the study is to detect the social pro-file of the Open Data movement activists, understanding how is it organized their network, what are the common purposes and solidarity models embodied by this type of movement, what are the resources mo-bilized and their strategies between on-line and off-line. The ODS case appears interesting for its evolu-tion, its strategy and organizational structure: an elitist and technocratic movement that aspires to a broad constituency. It is an expressive or a reformist movement, rather than an anti-system actor, with features that are similar to a lobby. The case study also shows all the typical characteristics of digital activism, with its fluid boundaries between ethical inspiration of civic engagement and individual interests